India: Indian Society of Agribusiness Professionals (ISAP) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Indian Society of Agribusiness Professionals (ISAP) aims to serve the farming community by providing access to appropriate agricultural technologies and market intelligence. ISAP is an NGO run by professionals from the agribusiness sector, including irrig